2022
DOI: 10.1186/s13071-022-05519-w
|View full text |Cite
|
Sign up to set email alerts
|

Tick microbial associations at the crossroad of horizontal and vertical transmission pathways

Abstract: Background Microbial communities can affect disease risk by interfering with the transmission or maintenance of pathogens in blood-feeding arthropods. Here, we investigated whether bacterial communities vary between Ixodes ricinus nymphs which were or were not infected with horizontally transmitted human pathogens. Methods Ticks from eight forest sites were tested for the presence of Borrelia burgdorferi sensu lato, Babesia spp., Anaplasma phagocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…For example, Rickettsia has been shown to enhance tick motility in Dermacentor variabilis [106]. Secondly, the possibility of interactions with other symbionts within the tick host should be explored as R. helvetica has been shown to modulate the microbiome of I. ricinus [107] and it has been found to be negatively correlated with certain symbionts such as Spiroplasma ixodetis and M. mitochondrii [31, 2]. It has been hypothesised that perhaps the biological roles of S. ixodetis and R. helvetica overlap, making their simultaneous maintenance energetically superfluous for the tick host [31], but this theory has yet to be proven.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Rickettsia has been shown to enhance tick motility in Dermacentor variabilis [106]. Secondly, the possibility of interactions with other symbionts within the tick host should be explored as R. helvetica has been shown to modulate the microbiome of I. ricinus [107] and it has been found to be negatively correlated with certain symbionts such as Spiroplasma ixodetis and M. mitochondrii [31, 2]. It has been hypothesised that perhaps the biological roles of S. ixodetis and R. helvetica overlap, making their simultaneous maintenance energetically superfluous for the tick host [31], but this theory has yet to be proven.…”
Section: Discussionmentioning
confidence: 99%
“…The most common tick-borne diseases associated with I. ricinus are Lyme disease (LB) which is caused by Borrelia burgdorferi sensu lato and tick-borne encephalitis (TBE), which is caused by tick-borne encephalitis virus [1]. In addition, I. ricinus transmits several emerging pathogens such as Rickettsia helvetica , Anaplasma phagocytophilum , Borrelia miyamotoi , Neoehrlichia mikurensis , and several Babesia species [2]. Infections with these pathogens have been associated with human disease in cross-sectional and case studies, but their pathogenic potential has not been fully understood [3, 4].…”
Section: Introductionmentioning
confidence: 99%
“…This negative association is suggestive of competition or niche partitioning between Spiroplasma and R . helvetica ( Krawczyk et al, 2022a , b ).…”
Section: Discussionmentioning
confidence: 99%
“…The same negative association was found in a previous study in which nearly 14,000 questing I . ricinus nymphs were screened by qPCR for tick-associated microorganisms ( Krawczyk et al, 2022b ). In contrast, other studies reported a positive association between Midichloria and Rickettsia spp., both in questing ticks and ticks collected from humans ( Budachetri et al, 2018 ; Lejal et al, 2021 ; Maitre et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…This bacterial genus is closely related to symbionts such as Midichloria mitochondrii . This species has been recently demonstrated to be positively associated with B. burgdorferi and Neoehrlichia mikurensis while being negatively associated with A. phagocytophilum ( 24 ). However, a method has been used which modeled co-occurrence of bacteria based on the chance of these bacteria being present together with M. mitochondrii .…”
Section: Discussionmentioning
confidence: 99%